PAI LEARNING TRANSFORMATION: ASWAJA INTEGRATION AND DIGITALIZATION IN THE 5.0 ERA - Eka P,W, Annisa Rezki; Mahiroh, Mar’ati; Wahab, Wahab (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The transformation of Islamic Religious Education (PAI) learning in the digital era aims to identify and categorise PAI materials, with a focus on strengthening Aswaja values as a valuable asset to strengthen the religious understanding of the younger generation. This research uses a qualitative approach with the type of content analysis, covering the mapping of PAI materials from elementary to high school levels. By utilising digital technology, PAI learning becomes more interactive and interesting, as well as expanding the reach of education. The integration of Ahlusunah Waljama'ah (Aswaja) materials in digital platforms allows the 5.0 generation to stay connected to Islamic traditions while developing digital literacy according to the demands of the times. This research offers a unique approach by integrating Aswaja materials into digital-based learning, which has rarely been explored. The aim is to develop a relevant PAI learning model and explain the integration of Aswaja materials with digital technology to fulfil the needs of the highly-connected generation 5.0. The results show that Aswaja material tends to be the core of PAI learning, which is relevant to the context of the 5.0 era. Transformation through digital media makes the concept of Aswaja more familiar to students, where the essence of religion must be strengthened in their minds and souls, while digital content serves as a supporting instrument. This research emphasises the importance of harmonisation between essential and instrumental aspects in PAI learning, where the role of the teacher becomes vital in this process. With the right approach, teachers can facilitate students to understand and internalise Aswaja values in a modern context, so that PAI learning is not only relevant but also attractive to all generations living in the digital era.